Prescribing pattern of antihypertensive drugs in diabetic patients of Southern Province, Kingdom of Saudi Arabia - Sirajudeen Shaik Alavudeen; Khaled Mohammed Alakhali; Shaik Mohammad Asif Ansari; Noohu Abdulla Khan
Background: Hypertension is extremely prevalent in patients with diabetes. Limited data exist on utilization patterns of antihypertensive in this population are consistent with evidence-based practice guidelines. Objective: To evaluate utilization patterns of antihypertensive agents among diabetic patients with hypertension. Design: Retrospective descriptive cross sectional. Patients / Participants: 149 patients with diabetes and hypertension from outpatient department at Family Medicine Hospital, Ahaderfieda. Khamis Mushait, K.S.A. Results: Over 43% of patients were receiving calcium channel blockers (CCB), 36.2 % of received angiotensin converting enzyme inhibitors (ACEI), followed by angiotensin receptor blockers (ARBs) (34.9%), diuretics (34.2%) and β -blockers (16.2%). Patients on monotherapy were mostly receiving CCB (34.3%) and ACEI (29.9%). The majority (55.03%) of treated patients were on multidrug regimens. In patients with coronary artery disease (CAD), a diuretic with ACEI (25%) and calcium channel blocker with angiotensin receptor blocker (25%) was most commonly prescribed. Conclusions: Patterns of antihypertensive therapy were generally consistent with international guidelines. Areas of improvement include increasing ACEI/ARB and diuretic use, decreasing the number of untreated patients, and increasing the proportion of patients with controlled BP in this population.